Legal Counsel Assistance in Court Proceedings in Criminal Cases - Singh, Rakhbir; Supardi; Prasetyo, Handoyo (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
The Indonesian Criminal Procedure Code (KUHAP) does not differentiate between ethnic groups or nationalities, ensuring that all individuals are treated equally before the court, whether in the District Court, High Court, or Supreme Court. Suspects or defendants are no longer viewed as "objects" but as "subjects" who possess rights and obligations, including the right to claim compensation or rehabilitation in cases of wrongful arrest, detention, prosecution, or legal judgment. The reality that many suspects/defendants are not accompanied by legal counsel during criminal proceedings raises significant questions about why the provisions of KUHAP are not adhered to. This thesis aims to analyze and elaborate on the regulations within KUHAP concerning the obligation of legal counsel to assist suspects/defendants in court proceedings and to analyze and elaborate on the rules that should govern the implementation of the obligation for legal counsel in criminal cases. The type of legal research employed in this work is normative legal research. This research is prescriptive in nature, aiming to provide a careful, comprehensive, and systematic description and analysis of the characteristics of individual or group behavior. Legal assistance by counsel is a fundamental right that must be fulfilled in every legal process, as stipulated in Article 56 of the Indonesian Criminal Procedure Code (KUHAP). Ironically, the hegemony of scientific studies tends to focus more on the subordination and compliance of citizens to the law rather than the subordination and compliance of law enforcement officials to the law itself. This obligation not only aims to protect the rights of suspects but also to ensure that the principles of justice and the protection of human rights are upheld within the criminal justice system in Indonesia.